Assessment of Quality of Life in Female Patients with Breast Cancer - Masarykova, Lucia; Lehocka, Lubica; Fulmekova, Magdalena; Polakova, Daniela (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Breast cancer is an oncological disease which affects to a large group of women. Despite being more aware of the disease now-a-days than it was in the past, a lot of women still die from the disease. The aim of the survey was to assess the quality of life among women suffering from breast cancer. To achieve this aim, a survey based on the EORTC QLQ-C30 questionnaire and the QLQ-BR23 module, which measured respondents´ physical, psychological and social functions, were used. Female breast cancer patients from the Tur?ianske Venue Citizens Association and those attending the Ligaprotirakovine Cancer Centre in Martin were included in the study. Elderly female patients average in their sixties, mostly with cancer in remission were involved. According to our findings, most of the female patients have had some difficulty doing physical activities and taking long strolls. Sleep problems and pain are also making the quality of their life worse. Lot of them have been getting a pain in their swollen arm and oversensitive breast. Most of the female patients reached an average QL2 score, which means an average quality of life. There were only two female patients with a QL2 score of 0, which means a very bad quality of life. However, three female patients had a QL2 score of 100, which means a very good quality of life. Based on our results, the quality of life for most of our female patients was average despite having some problems. Dhaka Univ. J. Pharm. Sci. 16(1): 29-36, 2017 (June)